Weak effects of conventional and biodegradable microplastics on marine microbial communities - Ulises Lora; Luca Schenone; Irene Forn; Francesc Peters; Jonna Piiparinen; Hermanni Kaartokallio; Maiju Lehtiniemi; Maria Montserrat Sala (Frontiers in Marine Science)
Microplastics are ubiquitous in marine ecosystems and are suitable matrices for bacterial attachment and growth. Studies on the microbes growing on plastics are mainly done using flow cytometry and massive sequencing, which do not allow for the quantification of specific groups and their activity. Here we present the results from a mesocosm experiment, designed to compare the effects of biodegradable and conventional microplastics on planktonic communities of the Baltic Sea. Our specific aim was to study the effects on bacterial activity and abundance using epifluorescence microscopy techniques. Specifically, we applied BONCAT-FISH which simultaneously allows for phylogenetic identification and the detection of the activity of individual bacterial cells. In our experiment, mesocosms were filled with Baltic brackish seawater and amended with 20 microplastic beads·ml-1 in triplicates for several treatments: (i) None (control), (ii) PS, (iii) PLGA and (iv) PS + PLGA. Our results show a low impact of the presence and quality of microplastics on marine bacterial communities during the first 11 days of exposure, with only weak differences in the activity of bacterial communities growing with biodegradable or conventional microplastics additions.